Association between the fatty liver index and the risk of fracture among individuals over the age of 50 years: a nationwide population-based study - Chung, Goh Eun; Cho, Eun Ju; Kim, Min Joo; Yoo, Jeong-Ju; Cho, Yuri; Lee, Kyu-na; Han, Kyungdo; Kim, Yoon Jun; Yoon, Jung-Hwan; Shin, Dong Wook; Yu, Su Jong (Frontiers in Endocrinology, 2023)
Background and purpose: The association between fatty liver and fracture risk has not been firmly established. In this study, we investigated the relationship between the fatty liver index (FLI) and the incidence of fractures among individuals ≥50 years of age, using a nationwide population-based cohort. Methods: Data from the Korean National Health Insurance System between January 2009 and December 2019 were analyzed using the Cox proportional hazards model. Fatty liver status was defined using FLI. Newly diagnosed fractures were identified based on insurance claim data. Results: Among the 3,384,457 individuals who met our inclusion criteria over the study period, 444,203 cases of incident fractures were identified over a median follow-up of 10.3 years. On multivariate analysis, the risk of fracture was significantly higher among individuals with a higher FLI score compared to those with an FLI <30, with adjusted hazard ratio [aHR] and 95% confidence interval [CI] as follows: FLI 30-59 group, aHR 1.04 and 95% CI 1.03-1.05; and FLI ≥60 group, aHR 1.12 and 95% CI 1.10–1.13). A higher FLI was associated with a greater risk of hip (aHR 1.23 and 1.52 for the FLI 30-59 and FLI ≥60 group, respectively) followed by vertebral fracture (aHR 1.08 and 1.16 for the FLI 30-59 and FLI ≥60 group, respectively). The association between the risk for fracture and FLI ≥60 was prominent for non-obese than obese individuals (aHR 1.25 and 95% CI, 1.22–1.27 versus 1.06 and 1.05–1.08, respectively). Conclusions: A high FLI is associated with an increased risk of hip and vertebral fractures among individuals ≥50 years of age, suggestive of an association between a higher FLI and osteoporotic fractures.